Correlating anthropometric parameters with lower limb muscle strength: on the example of female volleyball players - Bharathi Palani; Yeddanapalli Chinniah Louis Raj; Swamynathan Sanjaykumar (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose: This study aimed to investigate the relationship between anthropometric parameters, strength of the muscles of the lower limbs, and jump height among women volleyball players, with a focus on anthropometric parameters.